Effect of diversity on biomass across grasslands on the Mongolian Plateau: contrasting effects between plants and soil nematodes. (12th December 2015) - Chen, Dima; Cheng, Junhui; Chu, Pengfei; Mi, Jia; Hu, Shuijin; Xie, Yichun; Tuvshintogtokh, Indree; Bai, Yongfei
Abstract: Aim: To assess how the diversity of above‐ and below‐ground organisms changes along environmental gradients at the regional scale and whether the effects of diversity changes on biomass are similar for above‐ and below‐ground organisms. Location: Semi‐arid grasslands of the Mongolian Plateau. Methods: We investigated diversity (α‐, β‐ and γ‐) and biomass of plant and soil nematodes as well as environmental factors (climate, soil environment, and soil resource) at 44 field sites (220 plots) along a 2000‐km east–west transect and a 900‐km south–north transect across grasslands on the Mongolian Plateau. Regression was used to examine the relationships between diversity components and biomass of plants and nematodes. Hierarchical structural equation modelling (SEM) was performed to analyse the effects of environmental factors on diversity components and their linkages to biomass. Results: The biomass of plants and nematodes correlated positively with biodiversity measures for plants and nematodes except that nematode biomass decreased as nematode β‐diversity increased. The relationship between plant and soil nematodes was positive for biomass and for α‐ and γ‐diversity, but it was negative for β‐diversity. When considering the environmental factors, hierarchical SEM indicated that variation in plant or nematode γ‐diversity was associated with changes in climate, soil environment, and soil resources. Variation in plant or nematode α‐diversity was mainly associated with changes in γ‐diversity, while variation in the plant or nematode β‐diversity was mainly associated with changes in γ‐diversity and climate. The climate and soil resources explained most of the variation in plant biomass, whereas climate and α‐ and γ‐diversity explained most of the variation in nematode biomass. Surprisingly, plant biomass or diversity was only weakly related to soil nematodes when considering the environmental factors. Main conclusions: Diversity and biomass patterns of nematodes and perhaps of other below‐ground organisms are different from those of plants, and this difference is highly climate dependent. These findings suggest that a more complete understanding of diversity–biomass relationships will require further examination of more taxa across a broader range of environmental gradients.